Value Added of Paddy Seed Processing in Metro City - Teguh Budi Trisnanto (Politeknik Negeri Lampung, 2013)
Paddy seed breeding as an alternative income resource has a great opportunity to enhance farmer’s welfare. This research aims to analyze value added of paddy seed processing in Metro City. The research was conducted at Purwoasri, North Metro sub district on March until November 2012. Respondents are 21 members of Amurwat II farmer groups. Data was collected by survey method. Hayami method used to count the value added of paddy seed processing. Based on analysis, every kg input of paddy seed will produce 0,85 kg of certified paddy seed. The value added of paddy seed processing for each kilogram reached 1.532,94 Rupiahs. The ratio of value added toward product value is 28,63%, it means each 100,00 Rupiahs of product value will get value added Rp28,63. An employee who involved in paddy seed processing will get 169,91rupiahs for each kilogram of paddy seed input. Keyword: paddy seed, value added, farmer